The Lectin-Like Domain of Thrombomodulin Inhibits β1 Integrin-Dependent Binding of Human Breast Cancer-Derived Cell Lines to Fibronectin - Kawamoto, Eiji (Biomedicines, 2021)
Thrombomodulin is a molecule with anti-coagulant and anti-inflammatory properties. Recently, thrombomodulin was reported to be able to bind extracellular matrix proteins, such as fibronectin and collagen; however, whether thrombomodulin regulates the binding of human breast cancer-derived cell lines to the extracellular matrix remains unknown. To investigate this, we created an extracellular domain of thrombomodulin, TMD123-Fc, or domain deletion TM-Fc proteins (TM domain 12-Fc, TM domain 23-Fc) and examined their bindings to fibronectin in vitro by ELISA. The lectin-like domain of thrombomodulin was found to be essential for the binding of the extracellular domain of thrombomodulin to fibronectin. Using a V-well cell adhesion assay or flow cytometry analysis with fluorescent beads, we found that both TMD123-Fc and TMD12-Fc inhibited the binding between β1 integrin of human breast cancer-derived cell lines and fibronectin. Furthermore, TMD123-Fc and TMD12-Fc inhibited the binding of activated integrins to fibronectin under shear stress in the presence of Ca(2+) and Mg(2+) but not under strong integrin-activation conditions in the presence of Mg(2+) without Ca(2+). This suggests that thrombomodulin Fc fusion protein administered exogenously at a relatively early stage of inflammation may be applied to the development of new therapies that inhibit the binding of β1 integrin of breast cancer cell lines to fibronectin.